Vacuum switchgear - Greenwood, Allan 1923- (London, United Kingdom Institution of Engineering and Technology, 1994)
This book provides a broad perspective of vacuum switchgear drawn from the author's many years of expertise in this field. Allan Greenwood describes the development of the technology from the earliest beginning to the most recent designs now on offer by leading companies around the world.
Also available in print version.
Electronic reproduction.
Keywords: Vacuum switches; Electric switchgear; Electronic books